Why did we disown the Muslim brotherhood? - Gomaa, Omar; Ozalp, Mehmet (Penerbit Universiti Kebangsaan Malaysia, 2022)
Islamic movements had seemed to be ubiquitous, but a little work had profoundly looked at the internal issues of those movements that marked their increase and influence. Some Islamic movements are reckoned as intermediate, missionary, or terrorist Islamic groups. However, in this research paper, we ascertained that giving much attention to one of the most influential Islamic movements globally, the Muslim Brotherhood “Ikhwanul Muslimin”, will conceivably provide ample information for the literature regarding, not just Ikhwanul Muslimin. But generally, Islamic movements such as Ikhwanul Muslimin are considered the mother and fulcrum of political Islam and the emergence of Islamic movements. Conclusively, this research paper interviewed the exmembers of Ikhwanul Muslimin in exile to investigate why they disowned Ikhwanul Muslimin? Moreover, to closely understand the current role of those ex-members in society and whether they joined other Islamic movements, for instance. This research paper ascertained that Ikhwanul Muslimin leaders would likely play a business role by launching schools and companies in Turkey instead of leading the Egyptian opposition against al-Sisi.